Faktor Kemampuan Membaca Pemahaman Siswa Kelas V Sekolah Dasar - Nuramalina, Nuramalina; Dafit, Febrina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
Reading comprehension is one type of reading that is very important in the learning process. Each lesson contains reading comprehension. In the ability possessed by a person, it must contain factors that influence this ability, as well as the ability to read comprehension. This study aims to describe the factors that influence the reading comprehension ability of students in class V C SD Negeri 17 Pekanbaru. This research method is descriptive qualitative research with data collection techniques; interview, observation and documentation. The validity of the data used; technique triangulation, source triangulation and time triangulation. The data collection instruments used were interview guide sheets, observation and documentation. Based on the research results, it can be concluded that the factors that influence reading comprehension skills consist of internal and external factors. Internal factors are body condition, intelligence, motivation, interest and emotional maturity. While external factors, namely the family environment and school environment.